The Bridge of the Words : Between East and West - Ahmed, Khaled (Lahore Vanguard Books (Pvt) Ltd.)
A lot of excelent research exists in the west on the roots of the Indop-European group of languages. But no attempt has been made in Urdu and Persian to compile etymologies. But this book focouses on the Indop-European group of languages.
Include Bibliography.
Keywords: Indo-European Languages--Etymology